Władza rodzicielska jako przejaw relacji rodzicielstwa łączącej matkę i ojca - Łączkowska-Porawska, Małgorzata (PRAWO i WIĘŹ, 2025)
This paper addresses a specific type of legal relationship: parenthood, understood as a set of mutual rights and obligations between the mother and the father arising from the fact of having a child together. The scope of the analysis is limited to the rights and duties stemming from parental authority vested in both parents. Within the relationship between the mother and the father, the following are distinguished: the duty of mutual respect, the duty to cooperate in the best interests of the child, informational rights and obligations, and each parent’s right and duty to participate in, and to accept, the actions of the other. The study highlights that the appropriate attitude between parents arises both from the interdependent nature of their parenthood and from respect for the dignity and rights of the child.